PERTANGGUNGJAWABAN PIDANA DALAM TINDAKAN MEDIS: STUDI KRITIS TERHADAP PASAL-PASAL KRUSIAL DALAM UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Wicaksono, Emirza Nur (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2025)
This study analyzes the construction of criminal liability in medical actions under Law No. 17 of 2023 and assesses its implications for legal certainty, professional protection, and the doctor–patient relationship. Using a normative legal research method with doctrinal and conceptual approaches, the study finds that several provisions in the law particularly those related to professional standards, patient safety, medical records, informed consent, and criminal sanctions are ambiguous and potentially give rise to disproportionate criminalization. The lack of clarity regarding the threshold of negligence, the absence of an integrated professional assessment mechanism, and insufficient harmonization between health-criminal norms and the general criminal law framework create legal uncertainty for medical professionals. The legal enforcement implications of these conditions include the rise of defensive medicine, a shift in the doctor–patient relationship toward a more legalistic orientation, and the potential decline in the quality of healthcare services. The study recommends the development of more detailed implementing regulations, the harmonization of criminal norms, and the strengthening of the role of professional organizations in evidentiary processes to ensure proportional legal protection and a more equitable health system.